2016
DOI: 10.3109/02713683.2015.1098707
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Lipid Peroxidation Markers in the Tear Film and Ocular Surface of Patients with Non-Sjogren Syndrome: Potential Biomarkers for Dry Eye Disease

Abstract: The expression of late lipid peroxidation markers, 4-HNE and MDA, increases in the tear film and ocular surface of patients with dry eye. The levels correlate with various tear film and ocular surface parameters and may reflect the severity of dry eye disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
77
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 37 publications
0
77
1
1
Order By: Relevance
“…19 A limited number of publications investigating biomarkers in human tears for other steps in the lipid peroxidation pathway are available; increased expression was reported for two later stage products, 4-hydroxy-2-nonenal and malondialdehyde, in those with dry eye and increased age. 20,21 As HEL represents only one step in the lipid peroxidation pathway, future additional studies evaluating tears and ocular surface samples for different types of lipid peroxidation products would help clarify the potential significance of other lipid peroxidation effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 A limited number of publications investigating biomarkers in human tears for other steps in the lipid peroxidation pathway are available; increased expression was reported for two later stage products, 4-hydroxy-2-nonenal and malondialdehyde, in those with dry eye and increased age. 20,21 As HEL represents only one step in the lipid peroxidation pathway, future additional studies evaluating tears and ocular surface samples for different types of lipid peroxidation products would help clarify the potential significance of other lipid peroxidation effects.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,20,22,23 Reasons for this could be experimental differences in tear sample preparation and analysis, environmental-induced variation (i.e., previous reports are all from Japan), dietary differences, or genetic variation in HEL production. In support of diet-induced variation, it is well established that consumption of omega-6 fatty acids is much higher for those who choose a Western diet compared to those who consume a traditional Japanese diet.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that most reactive oxygen species (ROS) are highly reactive and short‐lived, it is difficult to detect them in biological substances . Therefore, measurement of the end products of lipid peroxidation is one of the most widely accepted approaches for evaluating oxidative damage .…”
Section: Discussionmentioning
confidence: 99%
“…Considering that most reactive oxygen species (ROS) are highly reactive and short‐lived, it is difficult to detect them in biological substances . Therefore, measurement of the end products of lipid peroxidation is one of the most widely accepted approaches for evaluating oxidative damage . 4‐HNE, which is commonly used as a marker of lipid peroxidation, as well as oxidative DNA and/or protein damage, is the major 4‐hydroxyalkenal end product generated by the decomposition of polyunsaturated fatty acids .…”
Section: Discussionmentioning
confidence: 99%
“…40,57,58 In vivo lipid oxidative injury has been observed in DED and Sjögren's syndrome patients. 59,60 In vitro studies further revealed that lipid and mitochondrial oxidative damage causes inflammation in HCE cells. 39,61 As mentioned above, various anti-inflammatory drugs, such as topical steroids and cyclosporine, have been widely used to treat DED, and studies have shown that anti-inflammatory treatment has a beneficial effect on tear secretion, tear film stability, and ocular surface integrity.…”
Section: Discussionmentioning
confidence: 99%